Prisotnost imen Ciril in Metod med Slovenci 20. in 21. stoletja - Osredkar, Mari Jože (Edinost in dialog, 2013)
Instances of the use of the names of the saints and the number of persons bearing their names in a specific geographical locale are signs of how individual saints are venerated, and, therefore, their popularity. In this study we will trace the use of the names of the Slavic brothers Saints Cyril and Methodius in Slovenia from 1930 to the present day. In the middle of the last century in Slovenia, relatively speaking, a lot of men bore Saints' names. However, in the last 70 years, evidence shows that fewer and few children have been so named by their parents; the proof can be found in the infrequency in which the names of these Slavic saints was entered into the Slovenian name registers. Today there is just a small sampling of newborns whose parents give the name of Cyril and Methodius. Exactly the same trend has been documented with the female form of the name of the Slavic apostles. We will argue that the diminution of the use of these names by parents of Christian families denotes a stronger and stronger presence of what we call secularization in contrast to traditional Catholic ways.
Keywords: Cyrillus, svetnik, 826-869; Methodius, svetnik, 815-885; svetniki; Slovenci; Slovenes; osebna imena; sekularizacija